Existence and regularity of solution for a model in magnetohydrodynamics. (January 2020) - Amrouche, Chérif; Boukassa, Saliha
Abstract: In this paper, we study a model of magnetohydrodynamics problem and prove the existence of weak solution to the stationary magnethohydrodynamic system in a three dimensional bounded domain Ω of class C 1, 1 . To our knowledge, all previous works consider the domain Ω simply-connected. Our proof is based on some weak estimates concerning vectors potential in negative Sobolev spaces. We also give some regularity results in L p -theory.